2018
DOI: 10.1017/prp.2018.4
|View full text |Cite
|
Sign up to set email alerts
|

New Paradigms for the Old Question: Challenging the Expectation Rule Held by Risky Decision-Making Theories

Abstract: I n risky decision making, whether decision makers follow an expectation rule as hypothesised by mainstream theories is a compelling question. To tackle this question and enrich our knowledge of the underlying mechanism of risky decision making, we developed a series of new experimental paradigms that directly examined the computation processes to systematically investigate the process of risky decision making and explore the boundary condition of expectation rule over the course of a decade. In this article, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 68 publications
0
7
0
Order By: Relevance
“…In addition, the experimental design in which the gain and loss trials were separately presented in different blocks might cause a contextual effect. Future studies should improve the experimental design by presenting the gain and loss trials in a randomized way within the same block, or draw from paradigms that directly examine the processes involved in risky decision making [ 73 ].…”
Section: Limitationsmentioning
confidence: 99%
“…In addition, the experimental design in which the gain and loss trials were separately presented in different blocks might cause a contextual effect. Future studies should improve the experimental design by presenting the gain and loss trials in a randomized way within the same block, or draw from paradigms that directly examine the processes involved in risky decision making [ 73 ].…”
Section: Limitationsmentioning
confidence: 99%
“…Moreover, the resulting estimated probabilities of gaining rewards were below half a chance. This pattern of findings eliminates the possibility that persuasion can enlarge the probabilities that participants' guesses correspond to each outcome and that a greater probability of gaining rewards indicates a higher tendency to play the game (see Zhou et al, 2018). The results showed a discrepancy with the work of Erev et al (2008), in which they suggested that presenting a possible outcome can increase people's subjective probability for that event.…”
Section: Probability and Confidence Evaluationmentioning
confidence: 88%
“…For choices between a sure thing x and a gamble (y, p), the original prospect theory [1] is equivalent to cumulative prospect theory [23]. Thus, people choose the option with the greatest overall prospect value [28].…”
Section: Prospect Theorymentioning
confidence: 99%
“…Taking the most controversial decision area (decision making under risk or uncertainty, for example), the representing system used by Montgomery will describe alternatives in two simple, risky dimensions [37]. In this case, even if some apparent compensatory rules, such as EV, EU, and SEU, are not included in his model of searching for a dominance structure, what is inferred from the think-aloud data as the compensatory rule being used by subjects might, in fact, be the non-compensatory one because what is seen as the two simple, risky dimensions (the probability of winning and the payoff) will be considered as only one dimension (possibleoutcome dimension) from the ETD theory's point of view [21,28,30,31,50]. Second, what is an operationally good dominance structure?…”
Section: Lexicographic Semiorder (Ls) Rulementioning
confidence: 99%